Reduction of the prime cost of thermal energy by the utilization of wind power plants in conjunction with boiler houses for heat supply in remote areas of the arctic zone of the Russian Federation (on the example of the Murmansk region) - A. V. Bezhan; Yu. N. Zvonareva; R. A. Ponamarev (Известия высших учебных заведений: Проблемы энергетики)
Providing comfortable living conditions of the local community is the important condition of the stable development and continued existence of remote areas of the Arctic Zone of the Russian Federation (AZRF) in modern Russia. The particular role played in this process is assigned to heat supply systems whose reliable and uninterrupted operation is fraught with various problems. The main ones are related to increased costs for the purchase of organic fuel and its delivery to remote areas. This circumstance leads to the fact that the prime cost of thermal energy is higher than the rates level, resulting in unprofitable activity of heat generating facilities, so their continued existence becomes impossible without government subsidies. Under these conditions one of the ways to save imported organic fuel and therefore reduce the prime cost of thermal energy can be the utilization of wind power plants (WPPs) in conjunction with boiler houses for heat supply in remote areas with increased wind potential. THE PURPOSE. It should be shown on the example of the Murmansk region that the utilization of WPPs in conjunction with boiler houses for heat supply in remote areas is a good decision to reduce the prime cost of thermal energy. METHODS. The comparison of the prime cost of thermal energy in a case of heat supply only from boiler houses with the one when utilizing WPPs in conjunction with boiler houses for heat supply. RESULTS. It is shown that the utilization of WPPs in conjunction with boiler houses with a capacity of more than 0.1 Gcal/h for heat supply in remote areas of the Murmansk region saves 60-90% of organic fuel worth 25,000-72,000 rubles/tce at boiler houses and thereby reduces the prime cost of thermal energy by 10-60%. An effect of the utilization of WPPs is reduced for boiler houses of lower capacity, with the lower the boiler house capacity, the more the utilization of WPP being economically impractical compared to a case of heat supply only from a boiler house. CONCLUSION. The results obtained allow us to assess the prospects of the utilization of WPPs in conjunction with boiler houses for heat supply in remote areas of AZRF in terms of the effectiveness of such utilization.